Interior Color Concept for Behavioral Therapy of Autistic Children Based on Lovass Method (ABA) - Sari, Sriti Mayang (Faculty of Psychology, Universitas Surabaya, 2010)
Autistic therapy room interior design is an element of environment created for autistic children. Elements constituting an interior design such as color can create an environment or atmosphere that supports the healing process. Color can be psychologically influential. Autistic patients possess an ability to be stimulated by psychological effect of colors. The purpose of this research was to create an interior design color concept of behavioral therapy rooms for autistic children based on Lovass/ABA method. The color concept or composition in accord with the autistic child’s character and Lovass/ABA method are the color with low intensity that can increase the ability to concentrate, improve the child’s emotion and give comfort. Desain interior ruang terapi autis merupakan lingkungan buatan yang keberadaannya berhubungan langsung dengan anak autis. Melalui elemen-elemen yang membentuk sebuah desain interior, seperti warna, dapat diciptakan sebuah lingkungan atau suasana ruang yang mendukung proses terapi. Warna dapat memberi pengaruh secara psikologis. Penderita autis memiliki kemampuan untuk merasakan rangsangan yang dihasilkan oleh efek psikologi warna. Tujuan yang ingin dicapai dari penelitian ini adalah membuat suatu konsep warna interior ruang terapi perilaku anak autis sesuai dengan metoda Lovass/ABA. Konsep warna atau komposisi warna dengan intensitas warna rendah interior ruang terapi yang sesuai dengan karakter anak autis dan metode Lovass/ABA adalah warna dan komposisi warna-warna yang dapat meningkatkan kemampuan konsentrasi, emosional, dan kenyamanan.